2021
DOI: 10.1159/000515235
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in <b><i>Staphylococcus aureus</i></b> Protein A Genotypes from Nose and Skin in Atopic Dermatitis Patients

Abstract: <b><i>Background:</i></b> <i>Staphylococcus aureus</i> colonization is associated with disease severity in patients with atopic dermatitis (AD). <b><i>Objective:</i></b> To investigate temporal variation in <i>S. aureus</i> protein A gene (<i>spa)</i>-types isolated from the nose and lesional skin and the correlation of <i>spa</i>-types with disease severity. <b><i>Results:</i></b> This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Among these patients, isolates from CC1, CC15, and CC45 were predominant [94]. Similar findings were obtained by van Mierlo et al in a population of 96 adults with AD from the Netherlands [104]. Benito et al also observed colonization of each individual with only one CC but reported a high clonal diversity among skin isolates compared with nasal isolates in AD patients from Spain.…”
Section: Lineages Of S Aureus That Colonize and Infect Patients With ...supporting
confidence: 84%
“…Among these patients, isolates from CC1, CC15, and CC45 were predominant [94]. Similar findings were obtained by van Mierlo et al in a population of 96 adults with AD from the Netherlands [104]. Benito et al also observed colonization of each individual with only one CC but reported a high clonal diversity among skin isolates compared with nasal isolates in AD patients from Spain.…”
Section: Lineages Of S Aureus That Colonize and Infect Patients With ...supporting
confidence: 84%
“…In studies described in 2021 by Masiuk et al ( 42 ), only two of 16 S. aureus from AD patients had a different genotype when nose and skin isolates were compared. Similarly, most AD patients have been found to be persistent S. aureus carriers with identical spa types in the nose and skin ( 43 ). The authors of previously published studies have also noted a high percentage of related skin and nasal isolates when they originated from one patient ( 4 , 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus is frequently isolated from the anterior nares, which is assumed to be the main reservoir for the spread of the pathogen-associated skin diseases such as atopic dermatitis ( van Mierlo et al, 2021 ). However, several S. aureus strains have been collected from pus cell of nodulocystic and pustular acne of volunteers ( Khan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is a systemic humoral response against commensal bacteria in healthy individuals (Sterlin et al, 2020). To examine the correlation between the abundance of bacteria and their antibody titers in humans, the level of IgG toward the antigens of C. acnes, S. aureus, and C. aurimucosum was evaluated by the reactivity of the human sera with the corresponding bacterial lysates.…”
Section: Acnes In Human Seramentioning
confidence: 99%